2014
DOI: 10.1371/journal.pmed.1001621
|View full text |Cite
|
Sign up to set email alerts
|

Lung Function and Incidence of Chronic Obstructive Pulmonary Disease after Improved Cooking Fuels and Kitchen Ventilation: A 9-Year Prospective Cohort Study

Abstract: Pixin Ran, Nanshan Zhong, and colleagues report that cleaner cooking fuels and improved ventilation were associated with better lung function and reduced COPD among a cohort of villagers in Southern China. Please see later in the article for the Editors' Summary

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
116
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(128 citation statements)
references
References 23 publications
(31 reference statements)
4
116
0
3
Order By: Relevance
“…Systemic and pulmonary inflammation is similar to cigarette smoke-induced disease [75,76], with less emphysema [77] and less rapid FEV1 decline [78]. Patients decline more slowly if the biomass exposure is reduced [28], but is not clear whether inhaled therapies used for "usual COPD" are of similar efficacy. The presence of BHR and overlap with asthma suggests that ICS might be an effective strategy, though no clinical trials have been reported yet.…”
Section: Subgroups With Implications For Treatmentmentioning
confidence: 99%
“…Systemic and pulmonary inflammation is similar to cigarette smoke-induced disease [75,76], with less emphysema [77] and less rapid FEV1 decline [78]. Patients decline more slowly if the biomass exposure is reduced [28], but is not clear whether inhaled therapies used for "usual COPD" are of similar efficacy. The presence of BHR and overlap with asthma suggests that ICS might be an effective strategy, though no clinical trials have been reported yet.…”
Section: Subgroups With Implications For Treatmentmentioning
confidence: 99%
“…More recently, in a prospective cohort of adults in southern China, switching to cleaner fuels (biogas) and/or improving ventilation of biomass smoke with the addition of a chimney or exhaust fan was associated with a slower decline in FEV 1 and fewer new cases of COPD over a 9-year period. 13 Th ese results are encouraging but need to be replicated in a study with an experimental design.…”
mentioning
confidence: 96%
“…Zhou et al also showed that there is a direct correlation between the extent of decreased pulmonary function and the time of exposure to biomaterial smoke. They reported this conclusion in a study on 966 patients with COPD and a positive history of exposure to biomaterial smoke [38]. Various mechanisms have been suggested to explain differences between respiratory systems in patients with previous exposure of biomaterial or cigarette smoke; although the composition of any type of smoke may be similar-or at least share common features-on the basis of the origin of biomaterial smoke, the combustive efficacy and the percentage of ambient humidity the effect on the respiratory system varies [26].…”
Section: Discussionmentioning
confidence: 81%